Analysis of Effective Location of Shear Wall for High Rise Building with U – Configuration - Mentari, Sekar; Nursani, Rosi (Semarang State University, 2021)
Indonesia is one of the countries that is prone to earthquakes. In addition to the dead loads, superimposed dead loads, and live loads, the design of buildings in Indonesia must be concerned with earthquake loads. Installing shear walls in the building structure as the Special Moment Frame Dual System is one of a solution to withstand earthquake loads. However, the location of shear walls must be considered, especially in buildings with horizontal irregularities. This study aims to determine the optimum location of the shear walls in a 10-storey building that has U-configuration with dynamic earthquake loads. This research is a numerical simulation ran by modelling the structure with software. To know the effect of the shear wall’s location on a building, several variations of the shear wall configuration with different positions have been conducted. It can be seen the lateral displacement of each floor and the shear force are the response structure to withstand the dynamic earthquake loads. Shear walls that are located close to the center of mass of the building are the optimum variation because the position of the shear wall is the closest to the core area of the building, which is the rotational axis of the building.